Transformation of the Velenje subsidence lake - Emil Šterbenk; Rudi Ramšak; Andrej Glinšek; Marko Mavec (Dela, 2017)
Lake Velenje formed as a result of the underground extraction of lignite in the Velenje coal mine. The article deals with certain special issues that have arisen as part of the process to transform the landscape from a riverine to a lake system as a result of mining and energy production. Anomalies in the lake system are explained drawing on research and monitoring of the properties and circulation of the lake water. As it was established on agricultural land, and due to intense pollution in the 1960s and 1970s, the lake initially was considered an environmental disaster; later, extensive environmental rehabilitation initiatives turned it into a recreational area.